The Effectiveness Of Thieves Strategy Towards Students’ Motivation In Reading Comprehension - Muhammad Sarifuddin; Mita Nunggrasari (JUPE : Jurnal Pendidikan Mandala, 2019)
This research aimed at finding out the effectiveness of using Thieves strategy toward students’ motivation in reading. The kind of this research was experimental reserach. The population of this reasearch was the first grade students’ of  SMK Darul Quran in academic year 2018/2019. This research took one class as the sample, which consisted of  18 students’. The data of this were primarily gathered from the result computation of  pre-test and post-test which given to the object of the research. In this research the researcher computed the data by using t-test formula. Based on the data analysis, he reearcher found t-test score 4.048 and t-table 1.740 with significant level 0,05%. It means that t-test was higher than t-table. Therefore, the conclusion that there was any significant effectiveness of  using Thieves strategy toward students’ motivation in reading comprehension.